Effect of Algal Extracts on the Growth of Tow Bacterial Types Isloated from Pollutants Discharge - Thaer Mohammed Ibrahim1, Raad Abdul Hadi Nayyef2, Buthaina Abdul- Aziz Hassan Al-Magdamy1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Effect of Chlorococcum humicola alcoholic algae extract was studied on the growth of, Pseudomonas aeruginosa, and Klebsiella pneumonia, which were isolated from contaminated water. The extract of Ch. humicola showed a high efficiency in reducing the numbers of the two types of bacteria. . The removal rate of K. pneumonia were 0.0, 48.4 and 57.0, The removal rate of P. aeruginosa were 63.1, 79.8 and 82.9% after24,48, 72 h respectively. The results improved that the K. pneumonia is more sensitive than P. aeruginosa for algae extract concentrations used in study ,and the beast effective time is 24h for the two bacterial species The aim of the study was to eliminate microorganisms using the Alcoholic algae extract. Especially P. aeruginosa and K. pneumonia of bacterial isolates that cause many diseases for human and animals.